KINDS OF SENTENCE (A Linguistic Study : Syntax and Semantic Point of View) - Eryon, Eryon; Sahrul, Sahrul (SIGEH ELT : Journal of Literature and Linguistics, 2022)
A sentence is a grammatically complete string of words expressing a complete thought. ThIs concept means tgat tgere wukk be kujekt varuiys strubg if wirds . This various string of words will cause different kinds of sentence. The kinds of sentence can be studied from syntacticÂ  and semantic point of view.This article discusses the kinds of sentence from syntax ad semantic point of view. It tries to discuss what kind of sentence a sentence belongs to. The discussion is based on theory of syntax and theory of semanticsÂ  and takes a concclussion.A sentence which has one clause and it is ended by a full stop and the speaker asserts its proposition will be a simple sentence, a statement sentence and a declarative sentence as well. Besude these, it may also belong to an analytic sentence if it is necessarily true as the result of the sense of the words in it.